The Effect of Acid Treatment on Metal Oxide Content of South Sulawesi Natural Clay - Sumiati Side; Suriati Eka Putri (Indonesian Journal of Fundamental Sciences, 2022)
Abstract. This study investigated the effect of adding acid on the metal oxide content of natural clay in Gowa Regency, South Sulawesi Province. The acid solutions used were sulfuric acid (H2SO4), hydrochloric acid (HCl), and nitric acid (HNO3) with a concentration of 3 M. The characterization of metal oxide content was carried out using XRF and morphological analysis of natural clay using SEM. The results showed that the impurity metal oxide content decreased after being treated with acid. The largest mass percent of silica alumina occurred in the HCl 3 M treatment with alumina mass percent of 20.27% and silica of 25.41%. The clay morphology looks different after being treated with acid for all types of acid solutions. The results of this study are expected to become recommendations for further research related to natural clay pretreatment both as a ceramic base material and as a catalyst support.